Network Of Islamic Education Ideology in Aceh Islamic Boarding Schools: A Systematic Literature Review - Ibda, Hamidulloh; Sofanudin, Aji; Syafi’, Moh.; Fikri, Mumtazul; Marzuki, Marzuki (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
This study reviewed 53 articles on Islamic education ideological networks in Islamic boarding schools in Aceh, Indonesia. This systematic literature review used the PRISMA protocol with the steps of identification, screening, eligibility, inclusion, abstraction, and data analysis assisted by the Publish or Perish 7, Mendeley, VOSviewer, and NVIVO 12 Plus applications. The search results obtained 544 Scopus-indexed articles, then filtered and 53 articles remained. The topic finding were: Islamic education ideology network, Aceh, Islamic boarding school, concept of Islamic education ideology, impact of Islam education ideology, Islam, pesantren, Indonesia, Islamic moderation, dayah, boarding school, which are directly connected, and Indonesian pesantren, anti-Muslim racism, formal religious education, Islamic culture, ISIS, terrorism, inter-religious relationship, Islamic religious college, cyberterrorism, deradicalization, curriculum development, curriculum, and dayah scholars. The findings of the articles were analyzed according to the topics defined through NVIVO 12 Plus and the results were described based on the research questions. The research findings explain that the ideology of Islamic education in Islamic boarding schools is a system of values, ideas, beliefs, and culture that is the basis for determining curriculum, teacher management, and learning. The ideological networks of Islamic boarding schools in Aceh are reform-modernist, traditionalist-Ahlussunnah Waljamaah, and Salafi-Wahabi which are developed based on typology, affiliation, characteristics, and curriculum. The ideology of Islamic education in Islamic boarding schools affects teachers, leaders, curriculum, learning, and society.